Beyond Representation: Tokenism and Epistemic Justice in Nursing Research - Debra Jackson; Tamara Power; Reakeeta Smallwood; Calvin Moorley; Denise Wilson; Roianne West; Debra Jones; Brendan McCormack (Nursing Inquiry, 2026)
ABSTRACT Tokenism has become an increasingly visible feature of contemporary research and scholarship, particularly in contexts where expectations of diversity and inclusion are institutionally embedded. While often presented as evidence of progress, tokenism raises critical questions about power, participation and the conditions under which knowledge is produced. Tokenism is more than simply a failure of inclusion, it is a functional feature of contemporary research systems, enabling the appearance of equity while preserving existing distributions of power. This paper examines tokenism as a form of inclusion that is more symbolic than substantive, projecting an image of progress while leaving existing hierarchies intact. We argue that tokenism in nursing research is not simply a problem of representation, but a form of epistemic injustice that shapes who participates, whose contributions are recognised and what knowledge is legitimised. In doing so, tokenism can obscure expertise, distort perceptions of competence and position individuals as representatives of identity rather than as authoritative contributors. These dynamics have ethical and epistemic consequences, including the reproduction of marginalisation, the generation of partial knowledge and the erosion of trust. Addressing tokenism requires a reorientation towards collaborative and justice‐oriented practices in which participation and epistemic authority is shared.